India - Syed, Afzal Basha (Jurnal Civil Engineering Study, 2025)
This research explores the viability of gastropod shell particulate (GSP), a calcium carbonate abundant residual from ocean refuse, as an ecologically responsible fractional substitute for cement in concrete. Ordinary Portland cement, a fundamental component in building, significantly impacts worldwide carbon dioxide release, highlighting the urgent need for eco-friendly alternatives. Finely ground gastropod shells possess cementitious properties due to their high calcium content, making them a promising supplementary cementitious material (SCM). Experimental evaluations were conducted by replacement of binder with GSP in different proportions (5, 10, 15, and 20% by weight) in concrete mixes. The study assessed the fresh and hardened properties of the modified concrete, including workability, compression strength, split tension strength, bending strength, and microstructural analysis through SEM (Scanning Electron Microscopy). Results revealed that a 15% replacement of cement with GSP achieved strength and durability comparable to conventional concrete while significantly reducing cement consumption and the associated carbon footprint. SEM analysis highlighted a denser, more cohesive microstructure in the 15% GSP concrete, with reduced voids and microcracks compared to the control sample, indicating improved matrix integrity. These findings establish the feasibility of GSP as a sustainable construction material, promoting the valorisation of marine waste while reducing environmental impact. This approach aligns with green construction practices and aids in fostering ecological progress within the building sector.